THE EFFECTS OF TAXATION ON FINANCIAL PERFORMANCE OF SMALL SCALE BUSINESSES IN BUGUJJU, CENTRAL DIVISION MUKONO DISTRICT. - Asekenye Pauline (My University, 2024)
This study aimed to investigate the effects of taxation on the financial performance of small scale businesses in Bugujju Mukono. The objectives of this study were three and they included; finding out the different types of taxes imposed for small-scale companies, finding out the effects of tax rates on the financial performance of small-scale businesses and, identifying the challenges associated with taxation and suggesting possible solutions to overcome them. The study used a cross-sectional survey design, including the quantitative research approach. A sample size of 93 respondents who were small-scale business owners involved in different businesses was used during the study and data was collected using questionnaires in Bugujju, Mukono. The findings of the study revealed the dissatisfaction with the types of taxes imposed on small-scale businesses by a majority of the respondents in terms of their burdensomeness and compliance costs on the business owners in the area studied. It further elaborated on the effect of tax rates on the financial performance of small-scale businesses, especially high tax rates, which were yet another concern by the respondents since these tax rates directly reduce the profitability and limit the growth of the small businesses in the study area. Finally, it was noted that the challenges associated with taxation such as quarterly payments and unpredictable tax liabilities disrupt cashflows and business operations in the area of study, Bugujju, Mukono. The study recommended tax authorities and government simplify the procedures and ways of computing and filling taxes to enhance understandability, authorities reduce the high tax rates imposed on small-scale businesses and also the need to effectively introduce and implement tax incentives in the form of tax holidays, and finally made emphasis on for tax education and sensitization of small business owners, through adverts and other programs that promote awareness among the different small scale business owners.